2020
DOI: 10.1111/jbfa.12419
|View full text |Cite
|
Sign up to set email alerts
|

Value creation around merger waves: The role of managerial compensation

Abstract: This paper examines the relation between executive compensation and value creation in merger waves. The sensitivity of CEO wealth to firm risk increases the likelihood of out‐of‐wave merger transactions but has no influence on in‐wave merger frequency. CEOs with compensation linked to firm risk have better out‐of‐wave merger performance in comparison to in‐wave mergers. We also present evidence that cross‐sectional acquirer return dispersion is greater for in‐wave acquisitions. Our results suggest that the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Accruals should increase in expected sales growth and in earnings as firms invest in working capital (Kothari et al 2005; Dechow et al 1998). Moreover, risk‐taking incentives are a function of investment opportunities (Guay 1999) and also incentivize managers towards growth (Croci and Petmezas 2015; Hillier et al 2020; Hanlon et al 2003). Indeed, Hribar and Nichols (2007) find improper discretionary accrual specifications produce spurious correlations between another attribute of equity compensation, delta, and earnings management.…”
Section: Prior Literaturementioning
confidence: 99%
“…Accruals should increase in expected sales growth and in earnings as firms invest in working capital (Kothari et al 2005; Dechow et al 1998). Moreover, risk‐taking incentives are a function of investment opportunities (Guay 1999) and also incentivize managers towards growth (Croci and Petmezas 2015; Hillier et al 2020; Hanlon et al 2003). Indeed, Hribar and Nichols (2007) find improper discretionary accrual specifications produce spurious correlations between another attribute of equity compensation, delta, and earnings management.…”
Section: Prior Literaturementioning
confidence: 99%
“…The regression results reveal that executive monetary compensation does not positively affect M&A performance, so hypothesis 1 is invalid. Hillier et al (2020) have shown that the monetary compensation system, as the most direct incentive method, can enhance executives’ work enthusiasm and promote executives’ efforts to improve corporate value [ 72 ]. However, the results of this study show that the monetary compensation system of listed media companies in China is ineffective during corporate transformation and upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…Although acquisitions are risky, they can also create value (Alexandridis et al., 2017; Hillier et al., 2020); firms can obtain resources and enter new markets through acquisitions (Berger et al., 2004). Therefore, some firms at risk of receiving a credit rating downgrade continue to pursue acquisitions; however, they may be more cautious when conducting acquisitions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%